Editorial (diségno, 2019)
The fifth issue of our journal is dedicated to the representation of the landscape, the environment and the territory, a theme very frequently dealt with, as multiscalar models and organisms are generally drawn and represented applying methods and principles that are widely diversified according to various arising needs or circumstances. At the same time, there are, in reality, objective difficulties in finding a common line of definition that brings together the three concepts of landscape –environment– territory, and this uncertainty derives precisely from the multi-dimensionality expressed by their conceptual depth, as well as from the ambiguity of these three terms when they are translated into other languages. (read more)